AKREDITASI PUSKESMAS, KEMAMPUAN KERJA, TINGKAT PENDIDIKAN DAN PENGARUHNYA TERHADAP KINERJA PEGAWAI UPT PUSKESMAS TEMBILAHAN KOTA INDRAGIRI HILIR RIAU - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
This study aims to analyze the effect of the center of society health accreditation, work ability, level of education on the performance of UPT Public Health Center employees at Tembilahan City, Indragiri Hilir, Riau. The population in this study were 70 people and all members of the population in this study became respondents. The results showed that UPT Public Health Center accreditation had a positive and significant impact on the performance of UPT Public Health Center employess at Tembilahan, Indragiri Hilir City, Riau. Work ability has a significant positive effect on the performance of UPT Public Health Center at Tembilahan, Indragiri Hilir City, Riau. The level of education has a positive and significant effect on the performance of UPT Public Health Center employess at Tembilahan, Indragiri Hilir City, Riau.